Inhibition Effect and Mechanism of Mesoporous Silica Hollow Nano-Spheres on Asphalt VOCs. Issue 2 (22nd March 2019) - Shu, Benan; Wu, Shaopeng; Li, Chao; Long, Yongshuang; Liu, Quantao
Abstract : In this paper, mesoporous silica hollow nano-spheres with continuous distributed pore diameters (MSHS) were simply synthesized by hydrothermal method. Then the effect of MSHS on inhibition of asphalt volatile organic compounds (VOCs) was studied by Pyrolysis-Gas chromatography/Mass spectrometry (GC-MS) test. In addition, scanning electron microscope (SEM), transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FT-IR) and brunauer-emmett-teller (BET) tests were conducted to analyze the inhibition mechanism. GC-MS result showed that the addition of MSHS could significantly reduce the emission of asphalt VOCs. Temperature played a decisive role in the emission amount of asphalt VOCs. The adsorption efficiencies of MSHS for alkanes, hydrocarbon derivatives and PAHs are different. Inhibition mechanism indicated that the reduction of emissions of asphalt VOCs is a result of physical adsorption, rarefied concentration adsorption and chemical adsorption caused by MSHS.